2020
DOI: 10.1016/j.immuni.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 VRC01 Germline-Targeting Immunogens Select Distinct Epitope-Specific B Cell Receptors

Abstract: Highlights d An epitope present on different immunogens selects for different targeted B cells d Each selected subpopulation comprises B cells with diverse affinities d The relative affinity dictates the fate of B cells following the initial selection d Developed 426cOD, a novel VRC01-class germline targeting immunogen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 64 publications
3
46
0
Order By: Relevance
“…Significant progress has been made in the design of immunogens that activate precursors of HIV bnAbs such as VRC01 and CH235.12, which target the CD4 receptor binding site and neutralize >90% of native isolates, and DH270 and BG18, which engage the glycan-V3 loop envelope (Env) region and have a global breadth of 55% and 64% respectively ( Dosenovic et al, 2015 ; Havenar-Daughton et al, 2018 ; LaBranche et al, 2019 ; Lin et al, 2020 ; Saunders et al, 2019 ; Steichen et al, 2016 , 2019 ; Tian et al, 2016 ). Immunogens targeting these antibodies have been shown to stimulate B cells displaying the respective bnAb UCAs in knockin mouse models and to promote the early development of bnAb lineages ( Dosenovic et al, 2015 ; Escolano et al, 2016 ; LaBranche et al, 2019 ; Lin et al, 2020 ; Saunders et al, 2019 ; Steichen et al, 2019 ; Tian et al, 2016 ). However, how to further induce maturation of activated bnAb precursors to attain significant neutralization breadth remains a major challenge for HIV vaccine development.…”
Section: Introductionmentioning
confidence: 99%
“…Significant progress has been made in the design of immunogens that activate precursors of HIV bnAbs such as VRC01 and CH235.12, which target the CD4 receptor binding site and neutralize >90% of native isolates, and DH270 and BG18, which engage the glycan-V3 loop envelope (Env) region and have a global breadth of 55% and 64% respectively ( Dosenovic et al, 2015 ; Havenar-Daughton et al, 2018 ; LaBranche et al, 2019 ; Lin et al, 2020 ; Saunders et al, 2019 ; Steichen et al, 2016 , 2019 ; Tian et al, 2016 ). Immunogens targeting these antibodies have been shown to stimulate B cells displaying the respective bnAb UCAs in knockin mouse models and to promote the early development of bnAb lineages ( Dosenovic et al, 2015 ; Escolano et al, 2016 ; LaBranche et al, 2019 ; Lin et al, 2020 ; Saunders et al, 2019 ; Steichen et al, 2019 ; Tian et al, 2016 ). However, how to further induce maturation of activated bnAb precursors to attain significant neutralization breadth remains a major challenge for HIV vaccine development.…”
Section: Introductionmentioning
confidence: 99%
“…Within the HIV space, VRC01-class bnAbs arise through a similar principle, wherein the human V H -gene IGHV1-2*02 is reproducibly deployed to structurally mimic the HIV receptor CD4, enabling exceptionally broad neutralization activity ( 15 , 24 ). Consequently, much effort has been applied to engineer germline stimulating immunogens to selectively prime and expand this genetically conserved bnAb pathway ( 33 49 ), and one candidate has entered a Phase 1 clinical trial (ClinicalTrials.gov, NCT03547245). More broadly, IGHV1-2*02 represents one of the more commonly used human antibody V H -genes ( 50 52 ) and we have recently demonstrated that this human V H -sequence also naturally endows germline repertoire with BCRs that target the conserved saccrolipid core of bacterial LPS, imparting a broad-spectrum extrafollicular response against bloodborne bacteria ( 53 ).…”
Section: Introductionmentioning
confidence: 99%
“…This mAb bound to recombinant iv12, but not to germline-targeting Env derivatives 426c.TM 4 ΔV1–3 or eOD-GT8 ( Figure S3 ). The absence of reactivity of PHVP2 to these two germline-targeting immunogens is not surprising, as the two immunogens are not expected to bind all available VH1–2 HC/5-aa LC BCRs ( Umotoy et al, 2019 ; Havenar-Daughton et al, 2018b ; Lin et al, 2020 ). Considering that we screened approximately 3.7 million naive B cells ( Table S2 ), and estimates of the frequency of VRC01 precursors range from ~1 in 300,000 based on eOD-GT8 sorting to ~1 in 10,000 based on unbiased high-throughput sorting ( Havenar-Daughton et al, 2018b ), these data indicate that none of the ai-mAbs tested was capable of efficiently engaging VRC01-class precursors in HIV-1-negative PBMC samples.…”
Section: Resultsmentioning
confidence: 99%
“…Although iv4 selects for short 5-aa CDRL3s, only a minority of these contain Glu96. Glu96 has been demonstrated to be important for binding of putative VRC01 precursors to germline-targeting Env ( Lin et al, 2020 ). Of the threeputative VRC01 precursorswe isolated in this study, PHVP6 was the only putative VRC01 precursor that bound a heterologous germline-targeting immunogen, and the only one with Glu96E.…”
Section: Discussionmentioning
confidence: 99%